Marginal reefs in the equatorial southwestern atlantic: benthic community heterogeneity, macroalgal blooms, and zooplankton biomass - Costa, Rhayany Juvêncio (2022)
Marginal reefs are those that occur in environments under restricted conditions, i.e., where corals occur close to environmental limits of survival or under conditions considered suboptimal, extreme or fluctuating. Thus, marginal reefs are generally associated with moderate turbidity, mesotrophic or eutrophic conditions, wide temperature variations, and/or resuspension of sediments, and are occupied by bioconstructing organisms adapted to such conditions. On these reefs there is generally a lower diversity of scleractinian corals that have adapted over evolutionary history. The resilience to environmental disturbance of coral species on marginal reefs reinforces the possible potential of these marine ecosystems as a refuge for part of the reef biodiversity in the face of ongoing climate change. However, despite growing global interest in how tropical reefs will be affected, little is known about the structure and dynamics of marginal reefs as compared to "classic" coral reefs, including aspects of the heterogeneity of benthic and planktonic communities, whose importance to reef ecology is recognized. In this context, Brazilian reefs are the only tropical reef environments in the Southwest Atlantic that are in an area considered marginal, and can be used as an important model to advance research. The objective of this research was to deepen the knowledge of the ecology of marginal reefs in the South Equatorial Atlantic from the study in three chapters in article format: (1) the spatial variation of the structure of benthic reef communities, (2) Rhizoclonium-like algal blooms, and (3) the variation in zooplankton biomass related to reef environments. Regarding benthic community structure (chapter 1), our results point to a strong spatial heterogeneity with reefs dominated by macroalgae (1 - 60%), filamentous algae (0 - 47%) and variable coverage of scleractinian corals (0 - 18%). On these reefs only four stress-tolerant massive corals occurred, with Siderastrea stellataand Montastraea cavernosa being the most abundant. The depth and the effect of swell-type waves that induce siltation of the shallower marginal reefs (16.6 - 16.7) represent important factors in the distribution of the benthic community such as sponges, algae, and corals. Another observed result refers to the occurrence of seasonal Rhizoclonium-like blooms in these marginal environments detailed in chapter 2 of the thesis. The macroalgae bloom was recorded, only between the months of May and August (2010 - 2018), forming dense mats near the reef substrate, in which they covered other organisms such as scleractinian corals, octocorals, sponges and other algae. Multivariate analysis indicates that blooms on these moderately turbid reefs are linked to increased atmospheric pressure, predominant north wind direction, and increased temperature range. Finally, in chapter 3, it was observed that in marginal reefs of turbid and low latitude zones the zooplankton biomass shows a heterogeneous distribution between different nets (65, 200 and 300 µm), with the oligotrophic characteristic of the waters and the presence of the reef formations seeming to play an important role in the distribution of the organic biomass. In this context, understanding the structure and occurrence of these benthic and planktonic communities and how they occur on marginal reefs represents a strategy of paramount importance to predict possible future scenarios, contributing to the management of these tropical reef ecosystems across the planet.